KOMUNIKASI INTERPERSONAL UNTUK ANAK-ANAK DI PANTI ASUHAN HATI SUCI - Paramita, Sinta; Michael; Teguh, Fiola; Susanto, Angeline; Vimala Yanthi, Valencia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Community Service Activities are carried out with the Hati Suci Orphanage Partners. Hati Suci Orphanage wants them to get a social environment that is generally obtained by children their age. In an effort to realize it, the Hati Suci Orphanage is faced with various challenges, one of which is the approach with children and the approach between one child and another, or how they carry out interpersonal communication. Interpersonal communication is an interaction process carried out between two or more people to convey messages that involve individuals as senders of messages and other individuals as recipients of messages that are useful for establishing positive social relationships. Therefore, we provide a solution by providing an understanding of how to carry out good interpersonal communication with others and people who are younger or older with the aim of training the self-confidence of the orphans. We do this understanding through the presentation of the material we have prepared in front of the orphans. The output we will produce is in the form of research articles published on kompas.com. The method of implementing this PKM activity has an implementation stage, that is, we conduct an informal presentation of interpersonal communication material to the children at the Hati Suci Orphanage. Participation of partners, namely providing space at the orphanage for presentation of material and scheduling meetings with orphanage children for presentation of the material. Description of the duties of team members, we have our respective roles in order to support PKM activities so that they run well. For additional outdoor plans, we will create a placard and flyer design regarding our material. In order to realize this PKM activity, we prepared this proposal with the title